A study of mapping of locally message exchanging algorithms on a loosely-coupled multiprocessor - Wada, Kumiko; Ichiyoshi, Nobuyuki (Shin-Sedai-Konpyūta-Gijutsu-Kaihatsu-Kikō <Tōkyō>: ICOT technical report, 1990)
Abstract: "Good load balance is the key to get the most from the processing power of parallel computers. Dynamic load balancing techniques have been developed and proved successful for tightly-coupled multiprocessors, and for loosely-coupled multiprocessors when the problem is composed of independent tasks with large granularity. But the problem of mapping intercommunicating processes on loosely-coupled multiprocessors has not been well explored. In this paper, we consider the problem when there is locality in message communication (locally message exchanging algorithms)